Design Aids for Single-Plate Framing Connections - Young, Ned W.; Disque, Robert O. (Engineering Journal, 1981)
Recently completed research at the University of Arizona has demonstrated that a properly designed single plate framing connection fabricated from A36 steel is safe and practical. To assist designers, detailers and estimators, the authors have developed tabular design aids which can significantly reduce the computation time required for the design of such connections.